Mediterranean Diet: Prevention of Colorectal Cancer - Donovan, Micah G.; Selmin, Ornella I.; Doetschman, Tom C.; Romagnolo, Donato F. (Frontiers in Nutrition, 2017)
Colorectal cancer (CRC) is the third most common cancer diagnosis and the second and third leading cause of cancer mortality in men and women, respectively. However, the majority of CRC cases are the result of sporadic tumorigenesis via the adenoma-carcinoma sequence. This process can take up to 20 y, suggesting an important window of opportunity exists for prevention such as switching toward healthier dietary patterns. The Mediterranean diet (MD) is a dietary pattern associated with various health benefits including protection against cardiovascular disease, diabetes, obesity, and various cancers. In this article, we review publications available in the PubMed database within the last 10 y that report on the impact of a MD eating pattern on prevention of CRC. To assist the reader with interpretation of the results and discussion, we first introduce indexes and scoring systems commonly used to experimentally determine adherence to a MD, followed by a brief introduction of the influence of the MD pattern on inflammatory bowel disease (IBD), which predisposes to CRC. Finally, we discuss key biological mechanisms through which specific bioactive food components commonly present in the MD are proposed to prevent or delay the development of CRC. We close with a discussion of future research frontiers in CRC prevention with particular reference to the role of epigenetic mechanisms and microbiome related to the MD eating pattern.